UKURAN PERUSAHAAN, KINERJA KEUANGAN, KEPUTUSAN INVESTASI DAN NILAI PERUSAHAAN (Studi Kasus pada Perusahaan Properti dan Real Estate di Bursa Efek Indonesia) - Teguh Erawati; Anita Primastiwi; Diyah Rahayu (Fakultas Ekonomi UNIBBA, 2022)
This study aims to examine the effect of size, financial performance, and investment decisions. The sample used in the study was the property and real estate company's annual report in 2016-2019. In this sampling technique the author uses purposive sampling techniques, find 24 samples according to criteria. This study uses multiple regression analysis. The result showed that size have no effect on firm value while financial performance and investment decisions has a positive effect on firm value.